Efektivitas Pemberian Jahe dan Gula Aren terhadap Emesis Gravidarum pada Ibu Hamil Trimester I di Puskesmas Klari - Jusmawati, Jusmawati; Sriwidianingsih, Teti (Universitas Malahayati, 2025)
ABSTRACT In the first trimester of pregnancy, problems are usually encountered that are often experienced by pregnant women, namely nausea and vomiting. However, nausea and vomiting that is quite severe is called hyperemesis gravidarum. Hyperemesis usually begins to occur at the 4th to 6th week of pregnancy, then the severity increases from the 8th to the 12th week, and usually ends at the 20th week or in the first to second trimester. The design of this research is a descriptive Quasy Experiment, with a two group only pre-post test design. The research was conducted in the Klari Community Health Center work area in June-July 2024. The population in this study was 74 pregnant women. Sample adequacy in this study used the Mann Whitney U-table. Wilcoxon test data analysis. The mean value of the pretest results for the group given the palm sugar ginger brew was 2.00, while the mean value of the posttest results was 1.25. The Wilcoxon test results have a significant p-value of 0.000 < 0.05. The mean value of the pretest results for the group that gave the ginger brew was 2.10, while the mean value of the posttest results was 1.55. The Wilcoxon test results have a significant p-value of 0.001 < 0.05. Mann Whitney test results obtained a significant p-value of 0.002 < 0.05. This means that there is a difference between giving palm sugar ginger tea and ginger tea, although both can affect the frequency of emesis gravidarum in pregnant women in the first trimester, but there are still differences. Keywords: Emesis Gravidarum, Ginger, Palm Sugar ABSTRAK Pada kehamilan trimester I, biasanya ditemui gangguan yang sering dialami oleh ibu hamil, yaitu mual dan muntah. Namun, mual dan muntah yang cukup parah disebut hiperemesis gravidarum. Hiperemesis biasanya mulai terjadi pada usia kehamilan minggu ke 4 sampai minggu ke 6, kemudian tingkat keparahannya meningkat pada minggu ke 8 sampai minggu ke 12, dan biasanya berakhir pada minggu ke 20 atau pada trimester pertama sampai trimester kedua. Desain penelitian ini adalah deskriptif Quasy Eksperimen, dengan desain two group only pre-post test desain.Penelitian dilakukan di wilayah kerja Puskesmas Klari dilaksanakan bulan Juni-Juli 2024. Populasi dalam penelitian ini adalah sebanyak 74 orang ibu hamil. Adekuatitas sampel dalam penelitian ini menggunakan tabel-U Mann Whitney. Analisis data uji Wilcoxon. Nilai mean hasil pretest kelompok pemberian seduhan jahe gula aren adalah 2.00 sedangkan nilai mean hasil posttest adalah 1.25. Pada hasil uji Wilcoxon signifikan p-value 0,000 < 0,05. nilai mean hasil pretest kelompok pemberian seduhan jahe adalah 2.10 sedangkan nilai mean hasil posttest adalah 1.55. Pada hasil uji Wilcoxon signifikan p-value 0,001 < 0,05. hasil uji Mann Whitney diperoleh angka significan p-value 0.002 < 0,05. Artinya ada perbedaan pemberian seduhan jahe gula aren dengan pemberian seduhan jahe walaupun sama-sama dapat mempengaruhi frekuensi emesis gravidarum pada ibu hamil trimester 1 namun tetap terdapat perbedaan. Kata Kunci: Emesis Gravidarum, Jahe, Gula Aren